Kasus Bupati Garut dan Fenomena Ahmad Fathanah: Pembelajaran Komunikasi Keluarga - Ulani Yunus (Humaniora, 2013)
Mass media reports about two males figure who have the power and wealth associated with the case in love relationship. It is not only seen as an “accident" for the women, it needs to be reviewed as further education. The purpose of research is to answer how the district regent of Garut case and the phenomenon of Ahmad Fathanah be a lesson for family communication. The method used is limited to library study, but it is also possible to continue in next research that is exploratory or explanatory research. Through this literature review, the researcher logic is a mainstay of the validity of research results. The results showed that the concept of true marriage must begin with the family, not only limited to verbal communication but also nonverbal. With the right family communication, stigma about women who just want male treasures is disallowed and can be positive thing for the women themselves. Recommendation is mass media help to achieve it through the selection of wise and polite language in framing the news about the women who seem to be "victims" of the power and wealth of men in the study case.